WHICH COUNTRY IS DESCRIBED HERE? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
'Geographical and climatic conditions do not help the work of the water distribution agencies. The chronic lack of rainfall is compounded by the fact that most agriculture is irrigated, and there is not enough water for simple human consumption. In...